Promising results of a clinical feasibility study: CIRBP as a potential biomarker in pediatric cardiac surgery - Lücht, Jana; Seiler, Raphael; Herre, Alexa Leona; Brankova, Liliya; Fritsche-Guenther, Raphaela; Kirwan, Jennifer; Huscher, Dörte; Münzfeld, Hanna; Berger, Felix; Photiadis, Joachim; Tong, Giang; Schmitt, Katharina R. L. (Frontiers in Cardiovascular Medicine, 2024)
Objective Cold-inducible RNA binding Protein (CIRBP) has been shown to be a potent inflammatory mediator and could serve as a novel biomarker for inflammation. Systemic inflammatory response syndrome (SIRS) and capillary leak syndrome (CLS) are frequent complications after pediatric cardiac surgery increasing morbidity, therefore early diagnosis and therapy is crucial. As CIRBP serum levels have not been analyzed in a pediatric population, we conducted a clinical feasibility establishing a customized magnetic bead panel analyzing CIRBP in pediatric patients undergoing cardiac surgery. Methods A prospective hypothesis generating observational clinical study was conducted at the German Heart Center Berlin during a period of 9 months starting in May 2020 (DRKS00020885, https://drks.de/search/de/trial/DRKS00020885). Serum samples were obtained before the cardiac operation, upon arrival at the pediatric intensive care unit, 6 and 24 h after the operation in patients up to 18 years of age with congenital heart disease (CHD). Customized multiplex magnetic bead-based immunoassay panels were developed to analyze CIRBP, Interleukin-1β (IL-1β), Interleukin-6 (IL-6), Interleukin-8 (IL-8), Interleukin-10 (IL-10), Monocyte chemotactic protein 1 (MCP-1), Syndecan-1 (SDC-1), Thrombomodulin (TM), Vascular endothelial growth factor (VEGF-A), Angiopoietin-2 (Ang-2), and Fibroblast growth factor 23 (FGF-23) in 25 µl serum using the Luminex MagPix® system. Results 19 patients representing a broad range of CHD (10 male patients, median age 2 years, 9 female patients, median age 3 years) were included in the feasibility study. CIRBP was detectable in the whole patient cohort. Relative to individual baseline values, CIRBP concentrations increased 6 h after operation and returned to baseline levels over time. IL-6, IL-8, IL-10, and MCP-1 concentrations were significantly increased after operation and except for MCP-1 concentrations stayed upregulated over time. SDC-1, TM, Ang-2, as well as FGF-23 concentrations were also significantly increased, whereas VEGF-A concentration was significantly decreased after surgery. Discussion Using customized magnetic bead panels, we were able to detect CIRBP in a minimal serum volume (25 µl) in all enrolled patients. To our knowledge this is the first clinical study to assess CIRBP serum concentrations in a pediatric population.